2021
DOI: 10.1002/cpdd.1057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Safety, Tolerability, and Disposition of Trazpiroben, a D2/D3 Receptor Antagonist: Phase I Single‐ and Multiple‐Ascending Dose Studies in Healthy Japanese Participants

Abstract: Trazpiroben (TAK-906) is a peripherally selective dopamine D 2 /D 3 receptor antagonist being developed to treat chronic gastroparesis. This phase I, randomized, double-blind, placebo-controlled, single-and multiple-ascending dose, parallelgroup study evaluated the safety, tolerability, pharmacokinetics, and pharmacodynamics of trazpiroben in healthy Japanese men.Findings were compared with those from a prior US trial in healthy individuals.Overall,24 participants were enrolled into 3 cohorts (each n = 8). Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Previous in vitro and animal studies demonstrated that trazpiroben selectively antagonizes D 2 /D 3 receptors with limited central nervous system penetrance, and also shows low affinity for the hERG potassium channel 16,17 . With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies 18–22 . A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro and animal studies demonstrated that trazpiroben selectively antagonizes D 2 /D 3 receptors with limited central nervous system penetrance, and also shows low affinity for the hERG potassium channel 16,17 . With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies 18–22 . A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function 23 .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 With respect to human studies, trazpiroben was well tolerated in phase 1 clinical trials (NCT03237156) and during phase 1 clinical pharmacology studies. [18][19][20][21][22] A phase 2a study (NCT03268941) assessed the safety profile, pharmacokinetics (PK), and pharmacodynamics of trazpiroben in patients with gastroparesis, with pharmacodynamics evaluated by the effect of trazpiroben on prolactin levels and gastric function. 23 This phase 2a study showed significantly improved volume-to-fullness following the nutrient drink test, and improved American Neurogastroenterology and Motility Society Gastroparesis Cardinal Symptom Index-Daily Diary (ANMS GCSI-DD) symptom scores with trazpiroben, further supporting its development to treat gastroparesis.…”
Section: Introductionmentioning
confidence: 99%